War, religion and service Huguenot soldiering, 1685 - 1713 - Glozier, Matthew; Onnekink, David 1971- (Politics and culture in north-west Europe, 1650 - 1720, 2007)
Introduction / Matthe Glozier and David Onnekink -- Huguenot soldiering c. 1560-1685 : the origins of a tradition / D.J.B. Trim -- Huguenots and Huguenot regiments in the British army, 1660-1702 : 'cometh the moment, cometh the men' / John Childs -- A study in misplaced loyalty : Louis de Durfort-Duras, Earl of Feversham (1640-1709) / Philip Rambaut -- 'The good Lord Galway' : the English and Irish careers of a Huguenot leader / Randolph Vigne -- 'Janisaries, and spahees and pretorian band' : perceptions of Huguenot soldiers in Williamite England / David Onnekink -- Schomberg, Ruvigny and the Huguenots in Ireland : William III's Irish war, 1689-91 / Harman Murtagh -- Huguenot soldiers in Dutch service : 'a good captain to disperse the royal troops' / Matthew Glozier and David Onnekink -- Au réfugié : Huguenot officers in The Hague, 1687 / Dianne W. Ressinger -- The refugees in the army of Brandenburg-Prussia : 'those unfortunate banished people from France' / Helmut Schmitter -- Integration and social assent of Huguenot soldiers in Brandenburg-Prussia : the impact of the Edict of Potsdam / Detlef Harms -- Huguenot soldiers in Brandenburg-Prussia under Friedrich Wilhelm and Friedrich III (1640-1713) : the state of research in German military, migration and confessional history / Matthias Asche -- 'The court at Celle is completely French' : Huguenot soldiers in the Duchy of Brunswick-Lüneburg / Andreas Flick -- Huguenots in the army of Savoy-Piedmont : Protestant soldiers and civilians in the Savoyard State in the seventeenth and eighteenth century / Paola Bianchi -- Huguenot soldiers in Russia : a study in military competence / Matthew Glozier